2010
DOI: 10.1074/jbc.m110.148767
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Accumulation of the RNA-binding Protein HuR Stabilizes the Ornithine Decarboxylase Transcript in a Murine Nonmelanoma Skin Cancer Model

Abstract: Ornithine decarboxylase (ODC) is the first and usually ratelimiting enzyme in the polyamine biosynthetic pathway. Under normal physiological conditions, polyamine content and ODC enzyme activity are highly regulated. However, the induction of ODC activity is an early step in neoplastic transformation. The studies described here use normal mouse keratinocytes (C5N cells), and spindle carcinoma cells (A5 cells) to explore the regulation of ODC in nonmelanoma skin cancer development. Previous results have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 50 publications
8
33
1
Order By: Relevance
“…We have shown previously using keratinocyte-derived cell lines that the RBP HuR associates with the ODC 3′UTR and stabilizes the ODC message in carcinoma cells but not in non-transformed cells [17]. To confirm that those results are not limited to the skin, we first performed an experiment designed to determine the intracellular localization of HuR in unstimulated parental and Ras12V-transformed RIE-1 cells (Figure 5A).…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…We have shown previously using keratinocyte-derived cell lines that the RBP HuR associates with the ODC 3′UTR and stabilizes the ODC message in carcinoma cells but not in non-transformed cells [17]. To confirm that those results are not limited to the skin, we first performed an experiment designed to determine the intracellular localization of HuR in unstimulated parental and Ras12V-transformed RIE-1 cells (Figure 5A).…”
Section: Resultsmentioning
confidence: 75%
“…We have recently shown that the ODC transcript is stabilized by the RBP HuR in cells derived from skin carcinomas [17]. To determine whether changes in rate of mRNA decay could contribute to the dramatic ODC activity induction seen in Ras12V cells, we examined ODC RNA stability in both cell lines after exposure to Actinomycin D. The t 1/2 for RIE-1 ODC RNA was 3.0 h (Figure 1B, C), while the t 1/2 in Ras12V cells was calculated to be 23.7 h, indicating an 8-fold increase in stability (Figure 1B, 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its expression and activity are induced in response to various external stimuli including tumor promoting agents [4, 5]. ODC is over-expressed in human non-melanoma skin cancers (NMSCs), including squamous cell carcinomas (SCCs) and basal cell carcinomas (BCCs), which are the most common human neoplasm [6]. Solar ultraviolet B (UVB), the major etiologic factor for NMSCs in humans induces ODC in the skin.…”
Section: Introductionmentioning
confidence: 99%